Electronic platform operators as participants of tax relations in the digital era (the case of professional income tax) - O. I. Lyutova (Правоприменение, 2021)
The subject. The research concerns analysis of legal status of a new participant of tax relations in the digital era - an operator of electronic platform.The purpose of the article is to confirm or disprove hypothesis that operators of electronic platforms are participants of tax relations and their rights and obligations must be described in tax legislation.The research methodology includes an interpretation of tax legislation, other legal acts governing the legal status of operators of electronic platforms, analysis of rights and obligations of other participants of tax relations.The main results and scope of their application. Due to the lack of an unambiguous definition of the legal status of operators of electronic platforms, obstacles are existed in the use of the transactional principle to taxation in case of professional income tax in Russia. Administration of this tax implies a complete absence of tax reporting as well as an unusual moment of the payment of this tax - at the time of the transaction, when self-employed taxpayer receives payment for his services by a consumer. This mechanism eliminates the unnecessarily complicated process of notifying the tax authorities about such transactions, but implies additional obligations to the operators of electronic platforms and the taxpayers themselves. It actualizes the necessity of detailed description of legal status of the operators of electronic platforms in tax legislation.Conclusions. The legal status of operators of electronic platforms in terms of belonging to the participants in tax relations already provided for in the Tax Code of the Russian Federation is not defined. Although they act as intermediaries in calculating and paying professional income tax. Such a lack creates a number of practical problems and does not contribute to the development of a transactional approach to taxation. At the present stage, it would be logical to recognize the operators of electronic platforms as tax representatives of taxpayers or withholding agents. According to the further development of the technical capabilities of tax administration, operators of electronic platforms may become a new participants of tax relations, who are conventionally called by the author «technological intermediaries».